2014
DOI: 10.1088/1758-5082/6/3/035019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of expansion and shear stress on a self-assembled endothelium mimicking nanomatrix coating for drug eluting stents in vitro and in vivo

Abstract: Coating stability is increasingly recognized as a concern impacting the long-term effectiveness of drug eluting stents (DES). In particular, unstable coatings have been brought into focus by a recent published report (JAMA 2012). Towards the goal of overcoming current challenges of DES performance, we have developed an endothelium mimicking nanomatrix coating composed of peptide amphiphiles that promote endothelialization, but limit smooth muscle cell proliferation and platelet adhesion. Here, we report a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…3335 Our previous studies have demonstrated that our nanomatrix coating forms a stable, smooth, uniform surface on stents; this may be a critical factor in prevention of inflammatory cell adhesion. 25 Thus, the nanomatrix coating itself may be protective under flow against inflammatory cell adhesion, although the addition of NO increased this protection. To investigate the effect of NO, the dynamic adhesion assay for PA-YK-NO coated stainless steel was repeated with the addition of 100 µM carboxy-PTIO, a well-known NO scavenger.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3335 Our previous studies have demonstrated that our nanomatrix coating forms a stable, smooth, uniform surface on stents; this may be a critical factor in prevention of inflammatory cell adhesion. 25 Thus, the nanomatrix coating itself may be protective under flow against inflammatory cell adhesion, although the addition of NO increased this protection. To investigate the effect of NO, the dynamic adhesion assay for PA-YK-NO coated stainless steel was repeated with the addition of 100 µM carboxy-PTIO, a well-known NO scavenger.…”
Section: Resultsmentioning
confidence: 99%
“…25 Briefly, the substrate mounted on a rotating mandrel attached to a motor was immersed within PA-YK or PA-YK-NO solution contained in an open top reservoir for 12 hours. The rotation ensured uniform coating of the nanomatrix on all substrate surfaces, while the open top of the reservoir facilitated evaporation.…”
Section: Methodsmentioning
confidence: 99%
“…39 Similarly, we have demonstrated that the PA-YK-NO was stable under physiologic conditions with very little flaking or cracking, even when compared to commercial medical device coatings. 40 In this study, we showed that the biomimetic nanomatrix did not affect the gas exchange properties of the microporous hollow fibers in bench-top studies.…”
Section: Discussionmentioning
confidence: 65%
“…These results also help explain the efficacy of the nanomatrix coated stent we observed in our previous preliminary in vivo rabbit iliac artery study, in which the nanomatrix-coated stent displayed reduced neointimal hyperplasia, reduced restenosis, and no evidence of thrombosis or fibrin deposition after 4 weeks. 26 Thus, these results could be translatable to in vivo settings.…”
Section: Resultsmentioning
confidence: 92%
“…24,27 Additionally, the nanomatrix is stable under physiological shear stresses, prevents and attenuates inflammatory responses, and enhances endothelial progenitor cell adhesion and differentiation. 25,26,28 In consideration of these results, it is essential to investigate the effects of nanomatrix-coated stents under physiological flow on endothelialization, smooth muscle cell migration, inflammation, and platelet adhesion.…”
Section: Introductionmentioning
confidence: 99%